Integrated Agriculture-Aquaculture (IAA) Farmer Manual (Arabic) - Nasr-Allah, Ahmed; Elewa, Ahmed; Sbaay, Ashraf; Habashi, Nada (WorldFish, 2024)
This guide shows the integration between fish and plants in integrated systems as well as their forms and how to reconcile them to achieve the maximum benefit for the farmer. It is produced and updated by WorldFish as a part of (F2R-CWANA) initiative Fragility to Resilience in Central and West Asia and North Africa in partnership with International Water Management Institute (IWMI) and the International Center for Agricultural Research in the Dry Areas (ICARDA).